Wide‐Field Three‐Dimensional Depth‐Invariant Cellular‐Resolution Imaging of the Human Retina. Issue 11 (15th January 2023) - Lee, ByungKun; Jeong, Sunhong; Lee, Joosung; Kim, Tae Shik; Braaf, Boy; Vakoc, Benjamin J.; Oh, Wang‐Yuhl
Abstract: Three‐dimensional (3D) cellular‐resolution imaging of the living human retina over a large field of view will bring a great impact in clinical ophthalmology, potentially finding new biomarkers for early diagnosis and improving the pathophysiological understanding of ocular diseases. While hardware‐based and computational adaptive optics (AO) optical coherence tomography (OCT) have been developed to achieve cellular‐resolution retinal imaging, these approaches support limited 3D imaging fields, and their high cost and intrinsic hardware complexity limit their practical utility. Here, this work demonstrates 3D depth‐invariant cellular‐resolution imaging of the living human retina over a 3 × 3 mm field of view using the first intrinsically phase‐stable multi‐MHz retinal swept‐source OCT and novel computational defocus and aberration correction methods. Single‐acquisition imaging of photoreceptor cells, retinal nerve fiber layer, and retinal capillaries is presented across unprecedented imaging fields. By providing wide‐field 3D cellular‐resolution imaging in the human retina using a standard point‐scan architecture routinely used in the clinic, this platform proposes a strategy for expanded utilization of high‐resolution retinal imaging in both research and clinical settings. Abstract : Three‐dimensional (3D) cellular‐resolution imaging of the living human retina over a large field of view will bring a great impact in clinical ophthalmology. Multi‐MHz phase‐stable wavelength‐swept laser and computational defocus and aberration correction enable single‐acquisition imaging of photoreceptor cells, ganglion cell axon bundles, and retinal capillaries across unprecedented imaging fields without bulky and costly adaptive optics (AO) hardware.